Chinese influence, U.S. linkages, or neither? Comparing regime changes in Myanmar and Thailand. Issue 3 (3rd April 2019) - Wong, Mathew Y. H.
ABSTRACT: This study examines the potential influence of foreign linkages on regime outcomes by comparing Myanmar and Thailand. Linkages with the West are supposed to facilitate democratization, whereas those with autocracies usually promote regime survival. This study focuses on Myanmar and Thailand's linkages with the U.S. and China, which at first sight seem to demonstrate the hypothesized effects. Myanmar gradually liberalized while strengthening its Western linkages, whereas Thailand experienced democratic breakdown amid a shift in alignment from the U.S. to China. However, in-depth analysis suggests that the influence of foreign linkages on domestic political change was minimal and that the relationship may very well be endogenous. The findings of this study call for a more careful theorization and handling of the external factors in studies of regime change and highlight the importance of simultaneously analyzing democratic and autocratic linkages.